2020
DOI: 10.1186/s13045-020-00887-1
|View full text |Cite
|
Sign up to set email alerts
|

Oct4 promotes M2 macrophage polarization through upregulation of macrophage colony-stimulating factor in lung cancer

Abstract: Background Expression of Oct4 maintains cancer stem cell (CSC)-like properties in lung cancer cells and is correlated with poor prognosis of lung adenocarcinoma. M2-type tumor-associated macrophages (TAMs) promote cancer cell migration and metastasis. Tumor microenvironments promote monocyte differentiation into M2 TAMs via a complex cytokine-based connection. We explored the role of Oct4 in cytokine secretion in lung cancer and its impact on M2 TAM polarization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 55 publications
2
72
0
Order By: Relevance
“…Even though the implication of CSF‐1 appears to be minor, a recent paper demonstrated that lung cancer cells expressing Oct4 stimulated the secretion of CSF‐1. As a consequence, CSF‐1 promoted M2 macrophages polarization leading to tumor growth and metastasis 103 .…”
Section: Overlapping and Non‐overlapping Functions Of Il‐34 And Csf‐1 In Diseasesmentioning
confidence: 99%
“…Even though the implication of CSF‐1 appears to be minor, a recent paper demonstrated that lung cancer cells expressing Oct4 stimulated the secretion of CSF‐1. As a consequence, CSF‐1 promoted M2 macrophages polarization leading to tumor growth and metastasis 103 .…”
Section: Overlapping and Non‐overlapping Functions Of Il‐34 And Csf‐1 In Diseasesmentioning
confidence: 99%
“…Moreover, Oct4 is involved in modulating the tumor microenvironment. Oct4 promotes M2 polarization by increasing M-CSF secretion, thus stimulating tumor metastasis [12]. These data imply the critical role of Oct4 in tumor metastasis.…”
Section: Introductionmentioning
confidence: 69%
“…Given that apoptosis causes the least immune reaction [24], it is critical to better understand the anti-apoptotic mechanism in order to develop effective strategies for cancer treatment. Previous studies have revealed that both Oct4 and Stat1 are overexpressed in lung adenocarcinoma and might play a role in cell survival [7,12,16,17]. Computational analysis shows that Oct4 may bind to the Stat1 promoter to transactivate Stat1 gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…After M-CSF binds to its receptor, downstream pathways PKC, PI3K and SFK could be activated to promote the migration of macrophages to tumor areas and transform them into M2 phenotype, and as mentioned earlier, they can also regulate the secretion of VEGF by macrophages and promote tumor angiogenesis [ 57 , 58 ]. For example, lung cancer cells express Oct4 to up-regulate the secretion of M-CSF, promoting M2 polarization, leading to cancer growth and metastasis, which has been verified in syngeneic mouse lung tumor model and clinical samples of non-small cell lung cancer [ 59 ]. Analogously, based on athymic BALB/c mouse model and RCC cell line, researchers found that RCC cells co-expressed M-CSF and its receptor.…”
Section: Macrophages Are Involved In Mediating Immune Suppressionmentioning
confidence: 99%